Accuracy of C-reactive Protein and Procalcitonin for Diagnosing Bacterial Infections Among Subjects With Persistent Fever in the Tropics. (24th August 2022) - Van Duffel, Lukas; Yansouni, Cedric P; Jacobs, Jan; Van Esbroeck, Marjan; Ramadan, Kadrie; Buyze, Jozefien; Tsoumanis, Achilleas; Barbé, Barbara; Boelaert, Marleen; Verdonck, Kristien; Chappuis, Francois; Bottieau, Emmanuel
Abstract: Background: In low-resource settings, inflammatory biomarkers can help identify patients with acute febrile illness who do not require antibiotics. Their use has not been studied in persistent fever (defined as fever lasting for ≥7 days at presentation). Methods: C-reactive protein (CRP) and procalcitonin (PCT) levels were measured in stored serum samples of patients with persistent fever prospectively enrolled in Cambodia, the Democratic Republic of Congo, Nepal, and Sudan. Diagnostic accuracy was assessed for identifying all bacterial infections and the subcategory of severe infections judged to require immediate antibiotics. Results: Among 1838 participants, CRP and PCT levels were determined in 1777 (96.7%) and 1711 (93.1%) samples, respectively, while white blood cell (WBC) count was available for 1762 (95.9%). Areas under the receiver operating characteristic curve for bacterial infections were higher for CRP (0.669) and WBC count (0.651) as compared with PCT (0.600; P <.001). Sensitivity for overall and severe bacterial infections was 76.3% (469/615) and 88.2% (194/220) for CRP >10 mg/L, 62.4% (380/609) and 76.8% (169/220) for PCT >0.1 µg/L, and 30.5% (184/604) and 43.7% (94/215) for WBC >11 000/µL, respectively. Initial CRP level was <10 mg/L in 45% of the participants who received antibiotics at first presentation. Conclusions: In patients with persistent fever, CRP and PCT showed higher sensitivity for bacterial infections than WBC count, applying commonly used cutoffs for normal values. A normal CRP value excluded the vast majority of severe infections and could therefore assist in deciding whether to withhold empiric antibiotics after cautious clinical assessment. Abstract : In 1838 patients with persistent (≥7 days) fever in tropical regions, C-reactive protein levels above 10 mg/L showed sensitivity of 88.2% for severe bacterial infections, and could have helped to avoid immediate antibiotic treatment in 45% of the cases.